Experiences in Building a Digital Twin Framework: Challenges and Possible Solutions - Gu, Rong; Barbuceanu, Teodor; Xiong, Ning; Seceleanu, Tiberiu (Proceedings : annual International Computer Software and Applications Conference, 2024)
Digital Twins (DTs) serve as the backbone of Industry 4.0, offering virtual representations of actual systems, enabling accurate simulations, analysis, and control. These representations help predict system behaviour, facilitate multiple real-time tests, and reduce risks and costs while identifying optimization areas. DTs meld cyber and physical realms, accelerating the design and modelling of sustainable innovations. Despite their potential, the complexity of DTs presents challenges in their industrial application. We continue here the development of our approach to build an adaptable and trustable framework for building and operating DT systems - A Digital Twin Framework for Dynamic and Robust Distributed Systems (D-RODS). D-RODS aims to address the challenges above, aiming to advance industrial digitalization and targeting areas like system efficiency, incorporating AI and verification techniques with formal support. We employ existing large-usage tools to illustrate the approach in development based on a synthetic adaptable use case.